2019
DOI: 10.1021/acs.analchem.9b01028
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Laser-Induced Fluorescence Detection at the Taylor Cone of Electrospray Ionization Mass Spectrometry

Abstract: Laser-induced fluorescence detection (LIF) is a powerful tool for the quantitative analysis of fluorescent molecules, widely used in glycan analysis with fluorophore labeled carbohydrates where each species has a common response factor. Electrospray ionization mass spectrometry (ESI-MS), on the other hand, while revealing important structural information about individual analytes, generally can have different response factors for different species. For simpler and improved quantitation with ESI-MS, laser-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…12 Recently, imaging LIF was also used to study the Taylor cone at the electrospray interface of a mass spectrometer with a high limit of detection (40 attomoles), ensuring simultaneous optical and MS detection of fluorophore-labeled sugars. 13 A previous study from our group also reported fluorescence from gaseous ions of a fluorescent dye under ambient conditions electrosprayed from a methanol solution. 3 As the ions get desolvated in the electrospray plume, solvent relaxation in their ground and excited electronic states disappears.…”
Section: Introductionmentioning
confidence: 94%
“…12 Recently, imaging LIF was also used to study the Taylor cone at the electrospray interface of a mass spectrometer with a high limit of detection (40 attomoles), ensuring simultaneous optical and MS detection of fluorophore-labeled sugars. 13 A previous study from our group also reported fluorescence from gaseous ions of a fluorescent dye under ambient conditions electrosprayed from a methanol solution. 3 As the ions get desolvated in the electrospray plume, solvent relaxation in their ground and excited electronic states disappears.…”
Section: Introductionmentioning
confidence: 94%
“…Both systems were capable to detect 13 glycans. A universal approach, independent of the ESI interface design, for simultaneous fluorescence‐based quantitative and MS‐based qualitative assessment of IgG released glycans was recently proposed [77]. With fluorophore labeled sugars, the authors used an imaging laser‐induced fluorescence (iLIF) system at the Taylor cone of the electrospray interface to collect fluorescent signal.…”
Section: Ce‐based Characterization Of Critical Quality Attributes (Cqas) Of Mab Productsmentioning
confidence: 99%
“…However, sample preparation can also be beneficial for MS detection to improve ionization efficiencies, reduce in-and post-source decay (e.g., sialic acids) and improve the glycan identification in MS/MS approaches, by creating more informative fragments [99,100]. Szarka et al demonstrated the possibility to perform simultaneous quantitative (optical) and qualitative (mass) analysis of APTS-labeled glycans using a novel imaging-LIF (iLIF) detector coupled to a CE-ESI-MS system [101]. By placing the iLIF detector at the Taylor cone of the electrospray interface it provides a quantitative fluorescence signal, prior to the MS-detection that is used for the structural analysis of the labeled glycans.…”
Section: Released Glycan Levelmentioning
confidence: 99%